Immunostimulant activities of a lipophilic muramyl dipeptide derivative and of desmuramyl peptidolipid analogs. - Parant, M A (1980)
The immunostimulant properties of a new muramyl dipeptide (MDP) derivative bearing a lipophilic moiety on the C-terminal end of the peptide chain are described. It is shown, in particular, that 1,O-(acetylmuramyl-L-alanyl-D-isoglutamine-L-alanyl)-glycerol-3-mycolate had increased immunostimulant activity in comparison with MDP. It induced hypersensitivity even when administered with an antigen in saline, and it gave higher protection against bacterial infections than did MDP. A quite unexpected finding was obtained with the corresponding desmuramyl compound 1,O-(L-alanyl-D-isoglutamine-L-alanyl)-glycerol-3-mycolate, which had no activity in producing humoral antibodies but was just as active as the muramic acid-containing compound in stimulating nonspecific resistance to bacterial infections. It was not pyrogenic. Modifications of the peptide moiety or the lipid moiety of this peptidolipid led to decrease, or even loss, of activity. These results show the importance of the N-acetylmuramyl moiety in MDP for humoral antibody production. The peptidolipid 1,O-(L-alanyl-D-isoglutamine-L-alanyl)-glycerol-3-mycolate is the first member of a new category of nonspecific immunostimulants.